Bacterial diversity and functional insights in the endosphere and rhizosphere of Adenosma bracteosum, an endangered species at different growth stages - To-Uyen-Thi Nguyen; Thanh-Dung Nguyen; Thi-Tho Nguyen; Thuy-Trang Pham; Thao-My-Thi Tran; Phu-Tho Nguyen; Thi-Pha Nguyen; Quoc-Khanh Hoang; Huu-Thanh Nguyen (Discover Soil)
Abstract Adenosma bracteosum Bonati, a member of the Scrophulariaceae family, is native to Tay Ninh Province, Vietnam, and is widely used in traditional medicine to treat liver and lung diseases. While the most research to date has focused on the plant’s bioactive compounds, less is known about its associated bacterial communities, particularly those in the endophytic and rhizosphere soil environments. This study aimed to characterize the bacterial communities in the roots and rhizosphere soil of Adenosma bracteosum at different developmental stages. A metagenomic analysis using 16S rDNA sequencing was conducted to characterize the microbial communities present in the rhizosphere of Adenosma bracteosum. The results indicated that younger plants hosted a greater diversity of bacterial phyla, with 36 phyla identified, compared to 31 phyla observed in older plants. Although some variations in distribution were observed, the overall bacterial composition of root and rhizosphere soil samples was largely similar, with predominant phyla including Proteobacteriota, Chloroflexota, Acidobacteriota, and Actinobacteriota. These findings suggest that endophytic bacteria within root tissues may derive from rhizosphere soil bacteria. Additionally, predictive metagenomic analysis indicates that the root endosphere exhibits a higher functional abundance of gene families, underscoring the critical functional roles that endophytic bacteria may play in supporting plant functions. These findings align with the theory that Adenosma bracteosum recruits bacteria from the rhizosphere into its endosphere. Furthermore, these microbial communities may play a role in enhancing the plant's adaptability to local environmental conditions, potentially contributing to the production of bioactive compounds in this medicinal plant.